Association between metabolic healthy obesity and female infertility: the national health and nutrition examination survey, 2013-2020 - Jing Tang; Yun Xu; Zhaorui Wang; Xiaohui Ji; Qi Qiu; Zhuoyao Mai; Jia Huang; Nengyong Ouyang; Hui Chen (BMC, 2023)
Abstract Background Obesity has been confirmed to be associated with infertility. However, the association between metabolically healthy obesity (MHO), a subset of obesity with no metabolic abnormalities, and female infertility has not yet been investigated. This study aimed to examine the association between MHO and the risk of female infertility among United States. Methods This study utilized a cross-sectional design and included 3542 women aged 20-45 years who were selected from the National Health and Nutrition Examination Survey (NHANES) 2013-2020 database. The association between MHO and the risk of infertility was evaluated using risk factor-adjusted logistic regression models. Results Higher BMI and WC were associated with increased infertility risk after adjusting for potential confounding factors (OR (95% CI): 1.04(1.02, 1.06), P = 0.001; OR (95% CI): 1.02 (1.01, 1.03), P < 0.001; respectively). After cross-classifying by metabolic health and obesity according to BMI and WC categories, individuals with MHO had a higher risk of infertility than those with MHN (OR (95% CI): 1.75(0.88, 3.50) for BMI criteria; OR (95% CI): 2.01(1.03, 3.95) for WC criteria). A positive linear relationship was observed between BMI/WC and infertility risk among metabolically healthy women (P non−linearity=0.306, 0.170; respectively). Conclusions MHO was associated with an increased risk of infertility among reproductive-aged women in the US. Obesity itself, regardless of metabolic health status, was associated with a higher infertility risk. Our results support implementing lifestyle changes aimed at achieving and maintaining a healthy body weight in all individuals, even those who are metabolically healthy.